GRAMMATICAL COHESION IN SUSAN CHOI’S FLASHLIGHT - Tomi Ilham; Dian Purnama Sari; Andry Azhari (LINGUA LITERA : journal of english linguistics and literature, 2022)
Abstract Grammatical cohesion is a study of the relation of grammatical elements that make the text unity. This research aimed to find out the types of grammatical cohesion used in the Flashlight short story by Susan Choi. There are four types of grammatical cohesion which are reference, substitution, ellipsis, and conjunction according to Halliday and Hasan’s theory. These types are very important in writing essays in order to make sentences related to each other and to enhance the reader’s understanding of the writers’ ideas. This research was qualitative research. The data was taken from the official website which was published on August 31, 2020. The data of this research was utterances in a short story. The data was analyzed based on the theory ofgrammatical cohesion by Halliday and Hasan. The research found 230 data. Reference was predominant with 109 occurrences (47%) that contained personal, demonstrative, and comparative reference which was realized by anaphoric and cataphoric. The conjunction was 121 occurrences (53%) with the additive, adversative, clausal, and temporal. The substitution was 1 occurrence (0,43%) with only verbal substitution where an ellipsis was not found. The finding of the research was not all types of grammatical cohesion found, namely nominal substitution, clausal substitution, nominal ellipsis, verbal ellipsis, and clausal ellipsis since the data was written text. Therefore, substitution and ellipsis were dominantly used in spoken text.